Pengaruh Ekstrak Sansevieria trifasciata melalui Diffuser terhadap Tingkat Karbon Monoksida (CO) Dalam Ruangan: Studi Eksperimental Percontohan N - Nurmila; Ibrahim, Juliani; Riksanto, Rolly; El Furqan, Dzar Fadli; Khadidjah, Siti; Nugraha, Ikhwandi Chandra (Journal of Health Science and Prevention, 2026)
Indoor air pollution, particularly from cigarette smoke, poses significant environmental health risks, including respiratory and cardiovascular effects. Sansevieria trifasciata has been reported as a natural air purifier capable of reducing volatile organic compounds and carbon monoxide (CO) in indoor environments. However, evidence regarding the effectiveness of plant-derived extracts combined with essential oils remains limited. Objective: To evaluate the effectiveness of Sansevieria trifasciata leaf extract, alone or in combination with essential oil, in reducing CO concentrations in enclosed indoor spaces exposed to cigarette smoke. Methods A quasi-experimental pre-test–post-test control group design was employed using four experimental rooms. Interventions included 60 mL S. trifasciata extract (PBL-21), 60 mL extract + 5 drops essential oil (PBL-20), 5 drops essential oil only (PBL-19), and control with no intervention (PBL-18). CO concentrations were measured before and after a 60-minute diffusion period using a portable CO analyzer. Data were analyzed using paired t-tests and ANOVA. Results: CO levels decreased by 37.5% in PBL-21, 68.8% in PBL-20, and 33.3% in PBL-19, while the control group showed minimal change. The combination of extract and essential oil demonstrated the greatest reduction, suggesting a synergistic effect. Conclusion: The combination of Sansevieria trifasciata extract and essential oil effectively reduced indoor CO levels from cigarette smoke in a quasi-experimental setting. These findings support the potential of plant- and essential oil-based interventions as eco-friendly, accessible strategies for improving indoor air quality. Further research with larger experimental designs and chemical profiling is recommended to validate and optimize these interventions.